Could you make a program for basic preparation for me? - Vuksanovikj, Vladimir; Jovanovski, Jovan; Nedelkovski, Vlatko (Faculty of physical education sport and health, Skopje, 2015)
Realization of the training process should be carefully pre-planned activity. Usually it is taken into consideration the ability of the athletes, that couch would like to modify. The whole idea of the training process should be written and clearly stated in the form of plan. In this way, it is easier to be understood of what, how much and how the couch and athlete work/train. Usually it is an annual plan and it last for one season. Therefore, within one season there are period of basic preparation, than competitive period, and at end is the rest period. When creating the basic preparations, one should take into consideration how much time its needed for realization of them, than when could be organized a friendly matches? When is the first official match? What is the age category of athletes? What is the previous experience of athletes (experienced / if they were in regular training process or not)? The rest is a creation of the author, who should have experience and knowledge of the methods for the transformation of motor skills and their implementation in the "match."
Keywords: basic preparations; periodization; training; motor skills; match